PEMANFAATAN FLIP CHART REMIND TERHADAP PENGETAHUAN DAN POLA KONSUMSI BUAH DAN SAYUR PADA PENDERITA HIPERTENSI DI PUSKESMAS PERUMNAS I PONTIANAK - Selvia Purba, Tiurma; Gambir, Jurianto (Pontianak Nutrition Journal, 2018)
Hypertension is a medical condition marked increase in blood pressure beyond normal limits. Consumption of foods high in fiber and minerals (potassium, magnesium, and calcium) is useful for lowering blood pressure. Therefore, patients with hypertension are advised to diet Dash with one principle is to consume fruits and vegetables 4-5 servings/day. Good level of knowledge about the food which affect hypertension will facilitate changes in food consumption behavior of patients with hypertension. The media used is flip charts. The purpose of this study to examine the use of flip charts remind of knowledge and consumption patterns fruit and vegetable in patients with hypertension in the Puskesmas Perumnas I West Pontianak. This type of research is Pre-Experiment with one group pretest posttest design. The test used is the paired t-testest and Wilcoxon. The number of samples was 20 samples and the research was conducted in June 2018. The results showed that there were differences in knowledge before and after the intervention (p= 0,000), while the pattern of consumption of fruits and vegetables showed no differences before and after the intervention (p= 0.184). The difference in average knowledge before and after the intervention was 25.33, while the difference in the average value of the pattern of fruit and vegetable consumption before and after the intervention was 33.33. Suggestions in this study for respondents, they can get used to consuming fruits and vegetables everyday by participating in the program GERMAS (Gerakan Masyarakat Hidup Sehat) which is held by health workers at the puskesmas and for further research in conducting research on knowledge and patterns of consumption fruits and vegetables, performed at least for 3 months.